Antioxidants of Eichhornia crassipes: The Worldâs Worst Aquatic Weed - N, Lata (Journal of Medical Biomedical and Applied Sciences, 2014)
The recent revival of interest in plant medicines across the globe and consequent pressure on precious herbal resources, calls for the use of plants through scientific screening and validation. Free radicals and reactive oxygen species (ROS) have aroused significant interest among scientists in the past decades. Their broad range of effects on the biological systems causing various diseases has drawn attention of many experimental works. The worldâs worst aquatic weed Eichhornia crassipes usually ranges from tropical desert to subtropical or warm temperate desert to rainforest zones. Ascorbic acid (vitamin C) one of the most extensively studied anti-oxidants has been detected in majority of plant cell types. Compounds of Quinones like anthraquinone considered to be a chemical antioxidant and possible therapeutic agents. Therefore, present investigation was planned to detect the presence of two bio-active compounds viz. Ascorbic acid and Quinones in the shoot and rhizome of Eichhornia crassipes by Thin Layer Chromatography (TLC) technique. The result obtained indicates that though plant is an aquatic weed is good services of phytochemicals needed for mainten-ance of good health, can also be exploited in manufacture of drugs. Its screening and scientific evaluation proves beneficial for the mankind along with the management of the plant.